Membedah Hadis Ipar adalah Maut: (Kritik Hadis dan Moralitas Keluarga Muslim) - Abd. Bashir Fatmal; La Ode Ismail Ahmad; Arifuddin Ahmad; Radhie Munadi (El Nubuwwah Jurnal Studi Hadis, 2024)
This study is motivated by the complexity of familial relationships in pre-Islamic Arab society and their ongoing transformation in the contemporary era. Interactions between non-mahram family members often lead to potential fitnah and conflict, necessitating a critical examination of the hadith, "The brother-in-law is a source of danger." This hadith carries profound meanings within the social and moral framework of Islam, thus requiring further analysis. This study investigates the authenticity of the hadith's sanad and matan using a qualitative literature review approach. The primary sources analyzed include Sahih Bukhari, Sahih Muslim, Sunan Tirmidhi, Sunan al-Darimi, and Musnad Ahmad, alongside theoretical frameworks related to sanad and matan criticism in hadith studies. The analysis reveals that this hadith is not merely a literal prohibition but rather a warning against the dangers of uncontrolled interactions within the family environment. Unrestricted interactions can lead to moral deviations, fitnah, and even the potential disintegration of the Islamic social order. These findings affirm that ethical boundaries in social interactions remain relevant across different eras, both in traditional societies and in the digital age, where communication is increasingly open and complex. The implications of this study underscore the importance of integrating Sharia values into social and educational policies to enhance ethical awareness and create a harmonious environment adaptable to contemporary challenges. Furthermore, this study contributes to the development of contemporary Islamic thought and encourages the reformulation of ethical policies in both family and professional settings.